Prospects of Single Cell Omics (SCO) Analysis for Investigating Nervous System Disorders - Muhammad Qasim Khan; Syeda Marriam Bakhtiar (Current Trends in OMICS, 2022)
Single Cell Omics (SCO) is an evolving field in biomedical research which offers prime application in neurosciences. The human nervous system is complex and shows variability in cell types. It includes neurons (functional components), glial cells (supporting cells), astrocytes (provide nourishment), oligodendrocytes (synthesize myelin sheath), and microglia (defense mechanism). To understand the functional and disease states of the nervous system, it is essential to investigate them at the single-cell level. It has been estimated that every 1 in 9 people is affected by mental or neurological disorders, including psychological disorders (generally referred to as mental disorders), psychotic disorders (involving psychosis), and neurological disorders (involving neurological factors), globally. These disorders have multifactorial etiology and are caused by genetic and environmental factors. Every disorder has distinct pathophysiology affecting multiple brain regions. SCO has excellent potential to provide insight regarding the diagnosis, pathophysiology, and treatment of neurological disorders. The stringent well directed SCO methods enhance the understanding of complex nervous system disorders, such as meningitis, stroke, schizophrenia, Parkinson’s disease, and Alzheimer’s disease, which paves the way for future research.